Perancangan produk tepat guna Pengupas, Pemipil dan Pengayak (3P) jagung berbasis Metode Value Engineering - Wesly Mailander Siagian; Ondo Pasuna Siagian; Tegar Arifin Prasetyo; Muhammad Ilham Maulana (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2026)
One way to improve productivity, efficiency, product quality, and product value, while empowering farmers in agricultural enterprises, is through the development of agricultural technology. Previous studies have designed agricultural technology in the form of a corn husking, shelling, and sifting machine, referred to as the 3P machine. However, based on evaluation results, the machine still requires further development in several critical aspects. This study aims to develop the corn 3P machine and evaluate its effectiveness and efficiency. The methods used in this study include value engineering, while the machine design was developed using SolidWorks software. The result of this study is an appropriate technology product in the form of an integrated corn 3P machine with a working capacity of up to 936 kg/hour. The relatively affordable manufacturing cost makes this technology an economical and practical solution with the potential for widespread adoption by corn farmers.Published Date: 2026-07-26